The “TFP” Fusion Technique for Posterior 360° Lumbar Fusion: a Combination of Open Decompression, Transforaminal Lumbar Interbody Fusion, and Facet Fusion with Percutaneous Pedicle Screw Fixation - Rao, Prashanth J (Orthop Surg, 2014)
Because degenerative spondylolithesis is prevalent in the elderly with associated osteoporosis, the rate of failure of pedicle screws is high; this leads to pseudoarthrosis and potentially requires reoperation. The burden of recurrent symptoms and reoperation is sufficiently significant to warrant prevention. We here describe a hybrid technique that involves a combination of a unilateral approach to bilateral decompression via a midline incision, transforaminal lumbar interbody fusion (TLIF), contralateral facet fusion, and percutaneously placed pedicle screws without compromising operative time and visualization. This approach is familiar to spine surgeons, adheres to the basic principles of minimally invasive spine surgery technique, minimizes dural and neural injury because of the unilateral TLIF approach, and provides a superior fusion construct because of facet fusion. In this procedure, patients with degenerative spondylolisthesis or scoliosis with moderate‐severe canal/foraminal stenosis undergo a midline unilateral TLIF and contralateral facet fusion with closure of the midline incision. Percutaneous pedicle screws are inserted under stereotactic guidance with reduction of the deformity using a pedicle screws construct. Rods are inserted percutaneously to link the pedicle screws. Image intensification is used to confirmed satisfactory screw placement and reduction of the spondylolisthesis.